Partisipasi Masyarakat Desa Tuafanu Dalam Pembangunan Pariwisata Pantai Oetune, Kabupaten Timor Tengah Selatan - Kulandima, Rendra Umbu Leha; Lasso, Aldi Herindra (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2023)
Community participation is essential in tourism development. The government plays a role in encouraging increased community participation. However, in practice, government involvement in management has the potential to have positive or negative impacts on community participation. The purpose of this study was to analyze the presence of the Tuafanu village community in the development of Oetune Beach tourism before and after being managed by the government. Through a qualitative descriptive method, this study examines the level of community participation in the development of the Oetune Beach tourist attraction. It is currently being managed by the government using the Arnstein participation ladder. The results of the study show that the participation of the Tuafanu village community at the start of Oetune Beach tourism development was at the level of degree of power. In other words, community power dropped to a pseudo-participation level after the government managed Oetune Beach. Therefore, the government's role focuses a lot on physical development needs to be followed by efforts to increase community participation so that it is maintained and continues increasing so that sustainable tourism completes